Behavior of platinum in the system of the matte-slag in the processing of copper-nickel ores - Fedorov, Sergey; Amdur, Alex; Pavlov, Valery; Krasikov, Sergey (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Copper-nickel sulfide ores are one of the main sources of platinum. The processes for extracting precious metal from such ores involves melting of a concentrate in electric ore smelting furnaces, where the melt is divided into matte and slag. Platinum is generally concentrated in matte; however, some its part remains in the slag, thus leading to metal losses. In order to reduce platinum losses, the forms of platinum in these phases should be studied. It was found that during the heating and melting of this ore in reducing atmospheres, iron, nickel, and copper are reduced. The mineral composition of matte has been studied. Platinum in matte is present in the form of intermetallides with Fe and Ni. The PtFe intermetallide is a dispersed needle formation with a length of 20 to 500 µm and a thickness of up to 10 µm. The size effect is revealed: the content of impurities in the PtFe intermetallide increases with decreasing the thickness of needle formations. The increase in the content of impurities in dispersed needle formations of platinum can be explained by an increase in the thermodynamic activity of the dispersed substance and a corresponding increase in solubility. It was found that matte drops, together with the associated Pt, Fe, and Ni intermetallide particles of no more than 5-7 µm in size, were carried into the slag by gas bubbles using flotation. The conditions for the rise of a matte drop, together with a bubble in the slag, consist in the fact that the adhesive force of the drop with the bubble and the buoyancy force acting on the bubble must be greater than the gravity of the drop.
Keywords: platinum, intermetallide, matte, slag, surface tension, flotation